POINT PREVALENCE OF PAEDIATRIC DENGUE VIRAL INFECTION - SUCHITRA, PUSAPATI; SRV, AMARTHYA; PADMAJA, I. JYOTHI; VIJAYALAKSHMI, PAYALA (International Journal of Current Pharmaceutical Research, 2023)
Objective: The study's objective is to evaluate the prevalence of dengue in the paediatric age group based on demographic data and clinical symptoms. Methods: The study was conducted in the Department of Paediatrics and Central Research Laboratory in a Tertiary Care Hospital in Visakhapatnam. Six months of data were collected from Jan 2022 to June 2022 and a maximum of 100 OPD/IPD cases have been registered during this study period. The entire medical history of all dengue cases, including signs and symptoms, method of diagnosis, management, length of stay, and clinical outcomes, were collected from patient information. NS1 antigen detection was performed by rapid test and Dengue ELISA was performed as a confirmatory test for the detection of IgG and IgM antibodies. Results: Among the 100 suspected cases of dengue reported to OPD/IPD, 83(83%) were confirmed as dengue positive, and 17(17%) were found to be non-dengue cases with ELISA. More cases were noticed in female children 52 (55%). Prevalence was more in the age group of 5-11 y 43 (52%). The majority number of cases were reported with fever 82 (98.8%) followed by symptoms like vomiting 41(49%), cold 19(16%), and cough 18(15%). Conclusion: Understanding dengue fever in children, including clinical symptoms, etiology, diagnostic testing, therapy, and prevention, is critical for lowering disease fatality rates.